Anaesthesia for the Stroke Patients New Challenges for Anaesthesiologist - Rahman, M Abdur (Journal of the Bangladesh Society of Anaesthesiologists, 2016)
Abstract not available Journal of Bangladesh Society of Anaesthesiologists 2014; 27(1): 1-2